"Utilização de grãos secos de destilaria com solúveis (DDGS) de milho na alimentação de vacas em lactação" - Werle, Caroline Hoscheid (2017)
The objective of this study was to evaluate the best level of DDGSinclusion in the diet of lactating cows. For this purpose, five lactating Dutch cows distributed in a 5x5 Latin square were used, fed diets containing 0%, 8%, 16%, 24% and 32% inclusion levels of DDGS in DM. The parameters evaluated were dry matter and nutrient intake and digestibility, microbial synthesis, milk production and composition, blood parameters and economic viability. The data were submitted to analysis of variance and polynomial regression considering the inclusion levels of DDGS at the 5% probability level. Thus, a reduction in the dry matter intake, organic matter, crude protein and nonfibrous carbohydrates and an increase in the intake of ethereal extract, neutral detergent fiber and total digestible nutrients were observed. The animals' body condition score was not altered despite the reduction of body weight to inclusion levels. The digestibilities of crude protein, neutral detergent fiber, total carbohydrates and total digestible nutrients increased linearly with inclusion of the coproduct in the diet. Dry matter digestibility was reduced according to the inclusion levels. Milk production was not influenced by DDGS inclusion levels. There was no change in allantoin excretions and in the production of microbial protein per kilogram of total digestible nutrients. Fasting plasma cholesterol levels at four hours after feeding presented a linear increasingeffect due to the fat content in the coproduct composition. The fasting creatinine content was reduced with increasing inclusion levels. The economic return was higher for the levels with inclusion of the coproduct in the diet. Thus, the use of DDGS in the feeding of lactating cows can be performed up to the 32%.